Bipolar resistive switching, synaptic plasticity and non-volatile memory effects in the solution-processed zinc oxide thin film. (February 2020) - Patil, V.L.; Patil, Aditya A.; Patil, S.V.; Khairnar, N.A.; Tarwal, N.L.; Vanalakar, S.A.; Bulakhe, R.N.; In, Insik; Patil, P.S.; Dongale, T.D.
Abstract: The memristive devices are getting a lot of interest in recent years due to its applications in the field of resistive memory and brain-inspired computing. In the present work, we have developed a ZnO memristive device using the reflux method. We have demonstrated non-volatile memory properties and mimicked the basic synaptic properties of using Al/ZnO/FTO thin film device. The structural, morphological and compositional studies of ZnO thin film were carried out by X-ray diffraction, scanning electron microscopy and X-ray photoelectron spectroscopy, respectively. The co-existence of analog and digital resistive switching in a ZnO memristive device was achieved by properly tuning the external electrical stimulus. The developed ZnO memristive device mimics the basic synaptic properties such as potentiation-depression, symmetric Hebbian and antisymmetric Hebbian learning rules at a lower voltage bias (±1 V to ± 3 V). Whereas, non-volatile memory properties (endurance and retention) were achieved at a higher voltage bias (±4 V to ± 6 V). The Al/ZnO/FTO thin film memory device shows good resistive switching memory properties such as 10 4 endurance cycles and 10 4  s retention period with good uniformity during the cycle to cycle operation. The detailed analysis of I–V results suggested that the Schottky conduction model is responsible for the analog mode of operation, whereas, space charge limited current governs the device dynamics during the digital mode of operation. A possible resistive switching model is also presented.